Development of Scalable Large-Area Solution-Processed Cu(In,Ga)(S,Se)2 Thin-Film Solar Cells Using Bar Coating Process - An, Seok-Chan; Kim, Da-Seul; Park, Sang Yeun; Min, Byoung Koun (AMER CHEMICAL SOC, 2025)
Vacuum-based processes for CIGS thin-film solar cells enable high efficiency and reproducibility, but their high cost and low material utilization limit their scalability for commercialization. To address these challenges, this study applied a solution-based bar coating process to evaluate its feasibility for large-area CIGS film production. To identify a suitable solvent for the process, theoretical and experimental analyses of key hydrodynamic parameters such as viscosity, Reynolds number, and Capillary number were conducted. As a result, 2-methoxyethanol (2Me) was identified as an optimal solvent that provides stable fluid behavior and uniform film formation. Using 2Me as the precursor solvent, CIG precursor films were deposited with thickness variation within ±2% on both small-area and 75 cm2 large-area substrates. After selenization, the films exhibited dense grains, a dominant crystalline phase, strong optical absorption (104–105 cm–1), and p-type conductivity. As a result, small-area devices achieved power conversion efficiencies of 7–8%, and the large-area substrate exhibited efficiency variation within ±4.5% across 12 positions, confirming high uniformity. These results demonstrate that the 2Me-based bar coating process ensures a uniform film quality, reproducible device performance, and scalability. Compared with conventional vacuum methods, this approach offers a low-cost, high-yield alternative suitable for large-area production of CIGS solar cells.